2020
DOI: 10.1007/s00162-019-00510-1
|View full text |Cite
|
Sign up to set email alerts
|

An immersed lifting and dragging line model for the vortex particle-mesh method

Abstract: The numerical study of the wake of full-scale slender devices such as aircraft wings and wind turbine blades requires high-fidelity large eddy simulation tools. The broad spectrum of scales involved entails the use of coarse-grain models for the devices. Actuator disk or line methods have been developed for that purpose, and are to date the most employed in that context. These methods transfer the force from the device to the fluid using 3D mollification functions. A novel immersed lifting and dragging line me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Sugar-Gabor et al [59] suggested a method where the unsteady wake was only accounted for in the outer 3D problem, allowing for roll and yaw kinematics. Lifting-line theory has also been used to model wings in large-scale simulations where resolving the chord-scale would be prohibitively expensive, for example, in Caprace et al [11].…”
Section: Introductionmentioning
confidence: 99%
“…Sugar-Gabor et al [59] suggested a method where the unsteady wake was only accounted for in the outer 3D problem, allowing for roll and yaw kinematics. Lifting-line theory has also been used to model wings in large-scale simulations where resolving the chord-scale would be prohibitively expensive, for example, in Caprace et al [11].…”
Section: Introductionmentioning
confidence: 99%
“…The simulations performed in this study allowed, in particular, to precisely describe the vortex dynamics involved in the generation of the two main wake vortices of the rotorcraft thanks to thorough 3-D visualizations. For further details about the ILL approach in a VPM framework, one also refers to [99], by the same authors.…”
Section: Aerodynamicsmentioning
confidence: 99%
“…An important difference between the diverse existing VIC schemes concerns the remeshing procedure in step 2. For example, in Caprace et al [99], the particles are remeshed on the underlying Cartesian grid only every 5 times steps, while in Mimeau et al [100] the remeshing procedure relocate the particles on the grid points every time steps, implying the presence of a particle at each node of the Cartesian mesh, at any time. In this particular latter case, one talks about "Semi-Lagrangian Vortex methods".…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be addressed that the current work mainly considers the kinematic representation of wall turbulence. The current V2V reconstruction is also different from the vorticity-based velocity reconstruction involved in the vortex method for simulating the Navier–Stokes equations (Leonard 1985; Koumoutsakos & Leonard 1995; Bernard 2013; Caprace, Winckelmans & Chatelain 2020). In those works, the velocity field is reconstructed based on the vorticity field.…”
Section: Introductionmentioning
confidence: 99%